Writing that breaks stones : African child soldier narratives - Uraizee, Joya F. (Joya Farooq), 1961- (East Lansing : Michigan State University Press, 2020)
"This book argues that the dominant literary mode that characterizes memoirs and novels about African child soldiers is ambiguity. It explores memoirs, such as Keitetsi's Child Soldier; Mehari's Heart of Fire; Beah's A Long Way Gone; Jal's and Davies's War Child; Akallo's and McDonnell's Girl Soldier; and Kamara's and McClelland's A Bite of the Mango, and compares these accounts with novels, such as Kourouma's Allah is Not Obliged; Dongala's Johnny Mad Dog; Iweala's Beasts of No Nation; Jarrett-Macauley's Moses, Citizen, and Me; Adichie's Half of a Yellow Sun; and Abani's Song for Night"--
War narratives and African children -- False combat and adolescent life writing -- Combat as backdrop in young adult life writing -- Narrative uncertainty in child soldier fiction -- Fictional dystopias in child soldier narratives.
Includes bibliographical references (pages 111-123) and index.
Keywords: Child soldiers -- Africa -- Personal narratives -- History and criticism; Child soldiers in literature; Ambiguity in literature; African literature -- 21st century -- History and criticism